Prevalence and Predictors of Depression, Anxiety, and Stress among Youth at the Time of COVID-19: An Online Cross-Sectional Multicountry Study. (6th October 2020) - Al Omari, Omar; Al Sabei, Sulaiman; Al Rawajfah, Omar; Abu Sharour, Loai; Aljohani, Khalid; Alomari, Khaled; Shkman, Lina; Al Dameery, Khloud; Saifan, Ahmed; Al Zubidi, Bushara; Anwar, Samh; Alhalaiqa, Fadwa
Abstract : Depression and anxiety are prevalent mental illnesses among young people. Crisis like the Coronavirus Disease 2019 (COVID-19) pandemic may increase the current prevalence of these illnesses. A cross-sectional, descriptive design was used to (1) explore the prevalence of depression, anxiety, and stress among youth and (2) identify to what extent certain variables related to COVID-19 could predict depression, anxiety, and stress (DAS) among young people in six different countries. Participants were requested to complete an online survey including demographics and the DAS scale. A total of 1, 057 participants from Oman (n = 155 ), Saudi Arabia (n = 121 ), Jordan (n = 332 ), Iraq (n = 117 ), United Arab Emirates (n = 147 ), and Egypt (n = 182 ) completed the study. The total prevalence of depression, anxiety, and stress was 57%, 40.5%, and 38.1%, respectively, with no significant differences between countries. Significant predictors of stress, anxiety, and depression were being female, being in contact with a friend and/or a family member with mental illness, being quarantined for 14 days, and using the internet. In conclusion, COVID-19 is an epidemiological crisis that is casting a shadow on youths' DAS. The restrictions and prolonged lockdowns imposed by COVID-19 are negatively impacting their level of DAS. Healthcare organisations, in collaboration with various sectors, are recommended to apply psychological first aid and design appropriate educational programmes to improve the mental health of youth.